VD_FINDINFO 65/2014/PHC vom 29. Oktober 2014 - VD Tribunal cantonal (2014)
AVOCAT, HONORAIRES CALCULÉS EN FONCTION DU RÉSULTAT POSITIF, MODÉRATION, DÉPENS | 45 al. 1 LPAv, 50 al. 1 LPAv, 50 al. 3 LPAv, 50 al. 4 LPAv, 48 LPA-VD, 55 LPA-VD